POEMS Syndrome in a Patient with Castleman Disease: A Case Report - Nayeem, Abu; Mandol, Gurudas; Zahid, Rasheed Imam; Habib, Md Ahsan; Baker, Issa Muhammad; Mohammad, Quazi Deen (Journal of Bangladesh College of Physicians and Surgeons, 2022)
POEMS syndrome is a rare multisystem disorder that clinically manifests as a paraneoplastic syndrome and monoclonal plasma cell dyscrasia. Its acronym is derived from its principal characteristics: polyneuropathy, organomegaly, endocrinopathy, M proteins, and skin changes. Here, a case of POEMS syndrome was reported also having features of Castleman disease. A 43-year-old man was admitted with weakness of all four limbs, tingling, heaviness, muscle cramps along with headache for the last 6 months; examination revealed flaccid quadriparesis, generalized areflexia with flexor plantar response, papilloedema, cervical lymphadenopathy, hepatomegaly, tender mass at the left parieto-occipital region, pitting edema and testicular atrophy. Laboratory tests revealed thrombocytosis, high blood sugar, hepatomegaly, lytic lesions at the left parietal bone, pelvis, and intraosseous mass in the Pareto-occipital region; nerve conduction study showed the demyelinating motor neuropathy without conduction block. Intraosseous mass biopsy showed solitary plasmacytoma and immunohistochemical markers positive for CD138 and Ki- 67 MUM-1 and lambda/kappa >10:1, suggesting plasma cell dyscrasia with lambda chain restriction. Biopsy from the cervical lymph node revealed features of Castleman disease. With these clinical and laboratory parameters, this case was finally diagnosed as POEMS syndrome in association with Castleman disease which is a common accompaniment with the syndrome. J Bangladesh Coll Phys Surg 2022; 40: 204-208